Impact of Skill Learning on Socio-Economic Development of ‎The Learners: A Bibliometric Analysis - Varma , N. Shradha; Kapoor , Dr. Namita (International Journal of Accounting and Economics Studies, 2025)
The purpose of this bibliometric analysis was to look at the body of research on socio-economic development through skill learning from ‎‎2000-2024 by mapping the evolution, trends, and opinions surrounding the importance of socio-economic development and the need for skill ‎development programs. Using the literature from various academic databases to conduct the analysis, this paper included research papers, ‎conference proceedings, and reports to identify the key research themes, contributions of the influential authors in this domain, as well as the ‎geographical distribution of the studies. The main conclusion of this analysis was that vocational training, education, and the development of ‎human capital are the key drivers of socio-economic development. The authors also noted an increasing trend in the literature around digital ‎skills, entrepreneurship, and industry-based training programs. The authors highlighted gaps in the literature regarding the lack of long-term ‎impact assessments of skill-training programs, as well as how gender and regions can affect the long-term impacts of skill development ‎activities. By using the bibliometric approach, the authors have provided a summary of the body of literature available regarding the role of ‎skill learning in the socio-economic development of an individual, and have created an opportunity for future researchers to continue to ‎explore the need for skill development as a means of achieving long-term sustainable socio-economic growth‎.